The effects of match congestion on physical performance in football referees - Moreno-Perez, V.; Courel-Ibáñez, J.; Del Coso, J.; Sánchez-Sánchez, J. (International Journal of Sports Medicine, 2022)
We examined the changes in performance during congested (two matches within a 7-day interval) and non-congested (one match within=7-day interval) fixtures in 17 elite football (soccer) referees during 181 official matches. External demands comprised 20 GPS-based metrics. Internal load was assessed by heart rate and rating of perceived exertion. Compared to non-congested fixtures, referees decreased their running distance at 21-24 km·h-1 (p=0.027, effect size [ES]=0.41) and > 24 km·h-1 (p=0.037, ES=0.28), the number of sprints (p=0.012, ES=0.29), and distance sprinting (p=0.022, ES=0.29) in congested matches. Most play metrics were lower in congested versus non-congested fixtures with low-to-moderate ES. During the 2nd half of non-congested fixtures, referees covered larger distances at low-speed running (p=0.025, ES=0.47). Match congestion due to officiating two matches less than a week apart caused a notable decrease in match running activity in professional football referees, especially at above 21 km·h-1. These data reiterate the need for specific conditioning and post-match recovery strategies in high-level referees to ensure optimal judgment performance favouring the quality of the competition. Governing bodies should take these outcomes into account when designating referees for a match.